2018
DOI: 10.1038/s12276-018-0097-y
|View full text |Cite
|
Sign up to set email alerts
|

Control of protein degradation by N-terminal acetylation and the N-end rule pathway

Abstract: Nα-terminal acetylation (Nt-acetylation) occurs very frequently and is found in most proteins in eukaryotes. Despite the pervasiveness and universality of Nt-acetylation, its general functions in terms of physiological outcomes remain largely elusive. However, several recent studies have revealed that Nt-acetylation has a significant impact on protein stability, activity, folding patterns, cellular localization, etc. In addition, Nt-acetylation marks specific proteins for degradation by a branch of the N-end r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 82 publications
(126 reference statements)
2
50
0
Order By: Relevance
“…Under lipid-rich conditions, PLIN2 contacts directly with neutral lipids and retains a SNARE complex protein, SNAP23, on the LD via their augmented interaction (38). Considering the degradation of free PLIN2 by the UPS in the cytosol, such lipid or protein bindings most likely induce its conformational change and, subsequently, shield the Ac/N-degron, thus protecting the PLIN2 protein from destruction by the TEB4-mediated Ac/N-end rule pathway, in agreement with the conditionality of Ac/N-degrons demonstrated in our previous works (12,17,18). Another plausible explanation for the stabilization of PLIN2 on LD most likely stems from the spatial segregation between LD-anchored PLIN2 and ER-embedded TEB4, which would prevent the interaction of the Ac/N-degron of PLIN2 with TEB4 E3 Ub ligase.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Under lipid-rich conditions, PLIN2 contacts directly with neutral lipids and retains a SNARE complex protein, SNAP23, on the LD via their augmented interaction (38). Considering the degradation of free PLIN2 by the UPS in the cytosol, such lipid or protein bindings most likely induce its conformational change and, subsequently, shield the Ac/N-degron, thus protecting the PLIN2 protein from destruction by the TEB4-mediated Ac/N-end rule pathway, in agreement with the conditionality of Ac/N-degrons demonstrated in our previous works (12,17,18). Another plausible explanation for the stabilization of PLIN2 on LD most likely stems from the spatial segregation between LD-anchored PLIN2 and ER-embedded TEB4, which would prevent the interaction of the Ac/N-degron of PLIN2 with TEB4 E3 Ub ligase.…”
Section: Discussionsupporting
confidence: 90%
“…7). In addition, it is noteworthy that A-PLIN2 is the first example of a NatA-dependent substrate of the Ac/N-end rule pathway to be identified in mammals, although the NatA complex acetylates 30 -40% of the N termini in the human proteome (12,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A less well-studied modification, N-terminal (Nt-) acetylation, has been described on PA-X ( Fig 1A). Nt-acetylation occurs cotranslationally on 80% of all proteins and may play roles in subcellular localization, protein stability, and protein-protein interactions (reviewed in [46]). A recent report revealed that PA-X Nt-acetylation is required for its activity [47].…”
Section: Co-and Posttranslational Modification Of Host Shutoff Rnasesmentioning
confidence: 99%
“…methionine aminopeptidases 1 and 2 (MAP1/2), which, in the absence of Nt-acetylation, can remove the initiator methionine (iMet) form the nascent chain. This leads to the exposure of the second residue, which in the case of NatB and NatC N-termini will lead to the exposure of an Arg/N-degron that can targets the protein for Ubr1 dependent degradation (Kats et al, 2018;Nguyen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%